Some Endogenous Hormones in Loquat - ERSOY, NILDA; KAYNAK, LAMI; KANKAYA, ABDULLAH (Asian Journal of Chemistry, 2010)
This work was carried out grown in an orchard of Citrus and Greenhouse Research Institute in Antalya. Fruit samples were taken from loquat trees (Eriobotrya japonica Lindl. cvs Gold Nugget and Akko XIII) on small, medium-size and ripe-fruit stages. Changes in the amounts of endogenous gibberellic acid (GA3), indole-3-acetic acid (IAA), abscisic acid (ABA) and zeatin (Z) during these growth periods of the loquat. IAA, GA3, ABA and Z were separated from plant extract and quantified by high performance liquid chromatography (HPLC) using a reversed-phase C18 column. Analysis of hormones was performed on a separate basis for seed and pericarp and levels of these hormones were found. According to the results, total-IAA was found high level in fruit flesh and seed samples in the small and mature loquat fruits. GA3 was low level in mature fruit but it was high in the seed samples in the same period. ABA level was found maximum in the small fruit in the both of the fruit flesh and seeds. Level of zeatin was found maximum in the small fruit' s flesh and seeds.